Do you agree or disagree with the assertion that calling a person with alcohol use disorder an “alcoholic” is detrimental for their care and engagement with treatment systems? (Translation: The University of Toledo Journal of Medical Sciences, 2025)
Essay Prompt: The passage to the right describes stigma as a major problem in the mental health field. Do you agree or disagree with the assertion that calling a person with alcohol use disorder an “alcoholic” is detrimental for their care and engagement with treatment systems? Please clearly state whether you agree or disagree and provide a justification for your answer. Please limit your response to the space provided below.
Keywords: NSCI1000